A new species of Mollinedia (Monimiaceae, Mollinedioideae, Mollinedieae) from Atlantic Rainforest, Brazil - de Lirio, Elton John; Peixoto, Ariane Luna (Phytotaxa, 2015)
In this contribution we describe and illustrate Mollinedia dolichotricha, a new species of the section Appendiculatae Perkins. The new species is morphologically close to M. argyrogyna. We also comment on the taxonomy, ecology, affinities with related species, and conservation status of the new species.